1989
DOI: 10.1152/ajpcell.1989.256.5.c1045
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Cl- transport in cultured cystic fibrosis airway epithelium

Abstract: Cultured human nasal epithelia derived from cystic fibrosis (CF) patients were studied with double-barreled, Cl- -selective microelectrodes to measure membrane potentials and intracellular Cl- activity (aClc). The aClc of CF cultures was 46.5 +/- 2.5 mM (n = 28), a value not significantly different from aClc of normal human nasal cells. Reduction of the luminal [Cl-] from 120 to 3 mM failed to reveal any apical Cl- permeability (conductive or nonconductive) in CF cultures. Bumetanide (10(-4) M, serosal) led to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 10 publications
3
45
0
1
Order By: Relevance
“…These data suggest that when K 1 efflux through the Nys pores is prevented by elevation of the luminal [K 1 ], the absolute magnitude of net Na 1 influx is revealed. As previously reported, elevation of the extracellular [K 1 ] did not affect HBE bioelectrics in the absence of Nys (20).…”
Section: Resultssupporting
confidence: 83%
“…These data suggest that when K 1 efflux through the Nys pores is prevented by elevation of the luminal [K 1 ], the absolute magnitude of net Na 1 influx is revealed. As previously reported, elevation of the extracellular [K 1 ] did not affect HBE bioelectrics in the absence of Nys (20).…”
Section: Resultssupporting
confidence: 83%
“…The same technique revealed the absence of Cl -secretion under conditions when ENaC was blocked with amiloride under basal or b-agonist-stimulated conditions. Subsequent double-barrelled microelectrode studies of freshly excised and cultured normal and CF cells detected a raised apical membrane Na z conductance in CF cells and a reduced or absent Cl -conductance [58][59][60][61]. Ultimately, studies of the apical membrane channels with patch clamp techniques revealed an increased activity of ENaC (increased open probability) in CF compared with normal cells [62].…”
Section: The Cell Biology Of Cystic Fibrosismentioning
confidence: 99%
“…Cultures of CF nasal epithelium (n ϭ 8, triplicate preparations) were mounted in a modified Ussing chamber. The CF apical membrane ionic conductance is virtually zero in the presence of luminal amiloride (10 Ϫ4 M), because CFTR is absent and Na ϩ channels are blocked (19), and basal calcium activated chloride conductance is minimal in the absence of a signal for increased intracellular Ca 2ϩ (20). Consequently, voltage changes induced by changes in apical vs. basolateral anion bath concentrations are likely dominated by bi-ionic PDs across the paracellular shunt (21).…”
Section: Assessment Of Paracellular Hcomentioning
confidence: 99%